2009
DOI: 10.1038/hr.2009.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salt substitute on pulse wave analysis among individuals at high cardiovascular risk in rural China: a randomized controlled trial

Abstract: Reduced-sodium, increased-potassium salt substitutes lower blood pressure but may also have direct effects on vascular structure and arterial function. This study aimed to test the effects of long-term salt substitution on indices of these outcomes. The China Salt Substitute Study was a randomized, controlled trial designed to establish the effects of salt substitute (65% sodium chloride, 25% potassium chloride, 10% magnesium sulfate) compared with regular salt (100% sodium chloride) on blood pressure among 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Previous studies showed no effect of potassium interventions on fasting AIx (15,39,40). One salt-substitution study (simultaneously reducing sodium and increasing potassium) showed significant improvements in measures of arterial stiffness (central pulse pressure and pulse wave reflection time) after 12 mo of intervention but did not see an effect on AIx (41).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed no effect of potassium interventions on fasting AIx (15,39,40). One salt-substitution study (simultaneously reducing sodium and increasing potassium) showed significant improvements in measures of arterial stiffness (central pulse pressure and pulse wave reflection time) after 12 mo of intervention but did not see an effect on AIx (41).…”
Section: Discussionmentioning
confidence: 99%
“…These data are in sharp contrast with the current literature, which shows a beneficial effect of salt restriction on arterial stiffness. 43,44 The authors provide no explanation for this puzzling finding. The examined population was very small, with approximately one dozen patients enrolled in each of the three studies.…”
Section: Study Limitations and Perspectivesmentioning
confidence: 93%
“…Njroge JN et al [15] and Ferreira-Sae MC et al [16] found that carotid intima-media thickness (C-IMT) was slightly increased in subjects with higher levels of salt consumption. The results of Hu Jet al [17] indicated that reduced salt intake was accompanied by a decrease in both central and peripheral blood pressure, as well as central pulse pressure. He FJ et al [18] observed a small decrease in pulse wave velocity following initiation of a low-salt diet.…”
Section: Introductionmentioning
confidence: 95%